Metal–organic framework-derived porous materials for catalysis - Chen, Yu-Zhen; Zhang, Rui; Jiao, Long; Jiang, Hai-Long (Coordination chemistry reviews, 2018)
Metal–organic frameworks (MOFs), constructed by metal ions/clusters and organic linkers, featuring crystalline porous structures, have been intensively employed as templates/precursors for the synthesis of diverse porous materials. The large surface area, high porosity and excellent tailorability of MOFs can be well inherited to their derivatives, making MOF-derived porous materials very promising for catalytic applications. Herein, we systematically summarize the versatile synthetic strategies to fabricate MOF-derived porous materials and give an overview on their recent progress on heterogeneous organocatalysis, photocatalysis and electrocatalysis. Finally, the challenges and prospects related to MOF-derived porous materials for catalysis are also discussed. [Display omitted] •A summary of the versatile synthetic strategies for MOF-derived porous materials.•Recent progress of diverse catalytic reactions over MOF-derived porous materials.•The challenges and prospects related to MOF-derived porous materials for catalysis. Metal–organic frameworks (MOFs), constructed by metal ions/clusters and organic linkers, featuring crystalline porous structures, have been intensively employed as templates/precursors for the synthesis of diverse porous materials including porous carbons, metal-based compounds (such as metal oxides/carbides/phosphides) and their composites. The large surface area, high porosity and excellent tailorability of MOFs can be well inherited to their derivatives, making MOF-derived porous materials very promising for catalytic applications. Herein, we systematically summarize the versatile synthetic strategies to fabricate MOF-derived porous materials and give an overview on their recent progress on organic heterogeneous catalysis, photocatalysis and electrocatalysis. Finally, the challenges and prospects related to MOF-derived porous materials for catalysis are also discussed.